Malignant Isolated Cortical Vein Thrombosis as the Initial Manifestation of Primary Antiphospholipid Syndrome: Lessons on Diagnosis and Management From a Case Report - Shen, Jie; Tao, Zi; Chen, Wei; Sun, Jing; Li, Yan; Fu, Fangwang (Frontiers in Immunology, 2022)
Background: Antiphospholipid syndrome (APS) with isolated cortical vein thrombosis (ICoVT) is an extremely rare but potentially malignant entity. It is particularly challenging to diagnose APS-related ICoVT because of the non-specific clinical manifestations and the frequent absence of typical neuroimaging. Moreover, there is currently limited knowledge of the clinical features and management strategies for the condition. Delays in diagnosis and treatment may lead to life-threatening consequences. Case presentation: We present a rare case of a 74-year-old Chinese woman who presented with sudden onset of headache and right arm weakness that mimicked acute ischemic stroke. Her initial computed tomography was unremarkable, and intravenous thrombolysis was performed. Serial neuroimages confirmed ICoVT 4 days after symptom onset, and low-molecular-weight heparin (LMWH) was started at a dose of 0.4 ml twice per day, according to the 2019 Chinese guidelines. The workup for the predisposing causes of ICoVT revealed triple positivity APS. LMWH dose was adjusted according to the anti-Xa chromogenic assay. However, the patient’s condition deteriorated rapidly, and there was a progressive enlargement of the venous infarction despite treatment with anticoagulants. Transtentorial herniation developed on day 12, and decompressive craniectomy was immediately performed. The patient’s symptoms did not improve significantly after surgery, and she remained aphasic and hemiplegic at the 3-month follow-up, with a modified Rankin Scale score of 5. Conclusion: ICoVT is a rare yet potentially fatal manifestation of APS, and its diagnosis and treatment are extremely challenging. Timely diagnosis, prompt treatment, and close monitoring are essential to improve the clinical prognosis of patients with APS-related ICoVT.